Comparison between mixed liquors of two side-stream membrane bioreactors treating wastewaters from waste management plants with high and low solids anaerobic digestion. (1st September 2016) - Zuriaga-Agustí, E.; Mendoza-Roca, J.A.; Bes-Piá, A.; Alonso-Molina, J.L.; Fernández-Giménez, E.; Álvarez-Requena, C.; Muñagorri-Mañueco, F.; Ortiz-Villalobos, G.
Abstract: In the last years, biological treatment plants for the previously separated organic fraction from municipal solid wastes (OFMSW) have gained importance. In these processes a liquid effluent (liquid fraction from the digestate and leachate from composting piles), which has to be treated previously to its discharge, is produced. In this paper, the characteristics of the mixed liquor from two full-scale membrane bioreactors treating the effluents of two OFMSW treatment plants have been evaluated in view to study their influence on membrane fouling in terms of filterability. For that, the mixed liquor samples have been ultrafiltrated in an UF laboratory plant. Besides, the effect of the influent characteristics to MBRs and the values of the chemical and physical parameters of the mixed liquors on the filterability have been studied. Results showed that the filterability of the mixed liquor was strongly influenced by the soluble microbial products in the mixed liquors and the influent characteristics to MBR. Permeate flux of MBR mixed liquor treating the most polluted wastewater was considerable the lowest (around 20 L/m 2  h for some samples), what was explained by viscosity and soluble microbial products concentration higher than those measured in other MBR mixed liquor. Graphical abstract: Highlights: Fouling in full-scale MBRs treating leachates of methane production plants is studied. Differences are found depending on methanation process (dry or wet). Membrane fouling is particularly severe for the dry process. High viscosity of the mixed liquor in dry process increases resistance to filtration. Differences in membrane fouling were not caused by extracted EPS.